Causes and Circumstances of Death in Portopulmonary Hypertension. Issue 7 (8th June 2021) - Sahay, Sandeep; Al Abdi, Sami; Melillo, Celia; Newman, Jennie; Dweik, Raed A.; Heresi, Gustavo A.; Tonelli, Adriano R.
Abstract : Background: The causes and circumstances surrounding death are poorly studied in patients with portopulmonary hypertension (PoPH). We sought to determine the specific reasons for dying and characteristics surrounding this process in patients with PoPH. Methods: All deaths of patients with PoPH followed in the Cleveland Clinic Pulmonary Vascular Program were prospectively reviewed by the pulmonary hypertension team between 1996 and 2020. Results: A total of 69 patients with PoPH (age 56.0 ± 8.9 y), with 49% females, were included. Causes of death were available in 52 (75%) patients, of these PoPH either directly or indirectly contributed to death in 13 of 52 (25%) of patients, meanwhile 39 of 52 (75%) of the patients died because of progressive liver disease and its related complications. Decompensated liver disease was the leading cause of death in this cohort 20 of 52 (38%), whereas 19 of 52 (37%) died because of conditions associated with liver disease. About half, 36 of 69 (52%) of patients died in a healthcare environment and 23 of 36 (64%) during a hospitalization at Cleveland Clinic. A total of 59 of 69 (74%) of patients received pulmonary arterial hypertension (PAH)-specific therapies. Six patients died after liver transplantation (in 3 death was related to PAH-related complications). Most of the patients in this cohort of PoPH patients were considered unsuitable for liver transplantation for a variety of reasons. Advanced healthcare directives were available in only 28% of patients. Conclusions: Most patients with PoPH died because of complications of their liver disease. PAH directly or indirectly contributed to death in a third of them. A quarter of them did not receive PAH-specific therapy before their death.